The Importance of Learning and Teaching English Language - Kydyrmoldina, M.; Nurzhanova, Zh. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
Communication in foreign languages and digital competence represent two of the eight key competences included in the Recommendation of the European Parliament and of the Council of December 18, 2006 referring to the strategies to be adopted by Member-States of the European Union, so that individuals could flexibly adapt to a rapidly changing and highly interconnected world. An ability to communicate in English is crucial in the modern world of mass global communication. Young people should be able to read, write and communicate in English as well as understand their teachers and peers at the high level. English is the language frequently used in communication, science, business, entertainment, travel and sport. Good knowledge of English provides young people with an access to these areas and enables them to continue their educational, economic, social and cultural development.